Chicken meat submitted to gamma radiation and packed with or without oxygen - Pelicia, K.; Garcia, E. A. [UNESP]; Molino, A. B. [UNESP]; Santos, G. C. [UNESP]; Vieira Filho, J. A. [UNESP]; Santos, T. A. [UNESP]; Berto, D. A. [UNESP] (FapUNIFESP (SciELO), 2015)
The objective of this study was to evaluate the effects on gamma radiation levels on the physical and microbiological characteristics of chicken breast meat. A completely randomized experimental design in a 4x2x3 factorial arrangement was adopted. Treatments consisted of four radiation concentrations (0, 2, 4, or 8kGy), two package sealing methods (with or without vacuum), and three storage times (01, 07, or 14 days), with ten replicates each, totaling 240 chicken breast fillets. Packaging and radiation had no influence (p>0.05) on chicken breast meat pH, water retention capacity, or presence of Salmonella spp. Breast fillets not submitted to radiation and vacuum packed presented higher water retention capacity (p<0.05) than those radiated at 4kGy and vacuum packed. Drip loss in fillets radiated at 8kGy and not vacuum packed was higher (p<0.05) than in non-radiated and non-vacuum packed fillets; however, both were not different from the other treatments. Coliform presence increased with storage time in non-radiated samples; however, when these were vacuum-packed, their development was slower. The results of the present experiment suggest that the use of a low radiation dose (2kGy), combined with vacuum packing, may minimize the harmful effects of storage on chicken breast fillets.
Keywords: Ionizing radiation; Poultry production; Storage period; Vacuum preservation